Lifestyle change reduces cardiometabolic risk factors and glucagon‐like peptide‐1 levels in obese first‐degree relatives of people with diabetes. Issue 4 (7th February 2017) - Bowes, A.; Begley, J.; Kerr, D.
Abstract: Background: Preventing type 2 diabetes in a real‐world setting remains challenging. The present study aimed to assess the effectiveness of a lifestyle‐based programme for individuals at high risk of developing type 2 diabetes as assessed by achieved weight loss, cardiovascular risk factors and glucagon‐like peptide‐1 (GLP‐1). Methods: Sixty‐six obese individuals with history of diabetes in first‐degree relatives participated in an 8‐month lifestyle programme consisting of 12 × 1.25 h group education sessions led by dietitian and a weekly exercise programme. Before and after comparisons were made of fasting blood glucose, insulin, HbA1c, lipids, GLP‐1 and quality of life (QoL). Results: Fifty‐four participants of whom the majority were women [47 females; mean (SD) body mass index 35.3 (2.8) kg m −2 ; age = 52 (10) years] completed the 8‐month programme. Mean (SD) weight loss was 10.1 (6.0) kg ( P < 0.001). Out of 54 participants, 36 lost more than 7% of their body weight and 47 lost more than 5%, with significant improvements in cardiovascular risk factors, glycaemia and QoL scores. The fall was observed in basal ( P < 0.05 versus baseline) but not stimulated GLP‐1 levels. In the subgroup of participants losing >10 kg, a correlation was found between weight change and change in both basal ( r = 0.61, P < 0.05) and stimulated ( r = 0.49, P < 0.05) GLP‐1. Conclusions: An evidence‐based lifestyle programme achieved sustained weight loss in obese first‐degree relatives of individuals with type 2 diabetes associated with improvements in cardiometabolic risk factors and QoL without the 'voltage drop' of less benefit commonly seen when moving from the clinical trial experience into the real world.